In-situ elongated aluminium borate grains toughening WC- 1.87 wt % Al2O3- 4.13 wt % ZrO2 composite via spark plasma sintering. Issue 16 (November 2019) - Li, Jingmao; Li, Xiaoqiang; Lai, Jiaming; Qiu, Hao; Cao, Ting
Abstract: In this work, a novel way was developed to facilitate the sintering of a binderless cemented carbide with Al2 O3 contain while improving its toughness. WC- 1.87 wt % Al2 O3 - 4.13 wt %ZrO2 cemented carbides with 1 wt % B2 O3 as additives were consolidated by high energy ball-milling and spark plasma sintering the as-milled composite powders. The effects of 1 wt % B2 O3 content on the sintering behaviour, microstructure and mechanical properties of the obtained cemented carbides were investigated. The presence of B2 O3 significantly lowers the sintering temperature by forming liquid phase and react with Al2 O3 which contributed to obtaining fully dense specimens at 1350 °C and maintains fine grain sizes of WC until the temperature exceeding 1450 °C. The sintering temperature of the specimens with optimum mechanical properties has been also reduced comparing that of the original WC- 1.87 wt % Al2 O3 - 4.13 wt %ZrO2 cemented carbides. Furthermore, the addition of B2 O3 triggered the reaction between B2 O3 and Al2 O3 resulting in forming in-situ elongated aluminium borate grains (A4 B2 O9 and A18 B4 O33 whiskers), which promoted the toughness. The specimens sintered at 1450 °C exhibited optimal mechanical properties: the Vickers hardness and fracture toughness were 19.26 GPa and 11.49 MPa m 1/2, respectively.